Hybrid Decision Support System Untuk Analisis Ketidakpastian Kecemasan Eksistensial Generasi Digital Berbasis Psikologi Eksistensial Dan Spiritualitas Al-Qur’an - M.Akbar Haskim; Afrida Dewi Efendi (Universitas Islam Indragiri, 2025)
The rapid advancement of digital technology has significantly reshaped psychological dynamics among the younger generation, leading to heightened levels of existential anxiety. Constant exposure to limitless information, algorithm-driven social pressures, and the instability of digital identity construction has created new forms of uncertainty that affect emotional, cognitive, and spiritual well-being. This study aims to analyze the complexity of existential anxiety in the digital generation through an integrative framework that combines existential psychology and Qur’anic spirituality within a Hybrid Decision Support System (HDSS). The purpose of this research is to formulate a systematic analytical model capable of identifying psychological indicators of existential anxiety while offering spiritually grounded reasoning derived from Qur’anic values. The study is expected to contribute both theoretically by strengthening interdisciplinary perspectives on digital-era mental health and practically, by providing conceptual foundations for the development of HDSS-based interventions that are contextually relevant for Muslim youth. This research uses a qualitative library research method, collecting data from books, scientific journals, credible online databases, and contemporary Islamic psychological literature. The findings indicate that integrating existential psychology with Qur’anic spirituality enhances analytical depth, enabling a more holistic understanding of uncertainty, meaninglessness, identity crisis, and loss of direction experienced by the digital generation. Furthermore, the proposed HDSS framework demonstrates potential as a structured reasoning system for evaluating existential symptoms and providing spiritually informed recommendations. The study concludes that addressing existential anxiety in digital society requires a balanced synergy between rational psychological analysis and transcendental spiritual guidance rooted in the Qur’an.